Black Noise, White Ears: Resilience, Rap, and the Killing of Jordan Davis - Cheng, William (Current Musicology, 2018)
I speak out of direct and particular anger at an academic conference, and a white woman comes up and says, “Tell me how you feel but don’t say it too harshly or I cannot hear you.” But is it my manner that keeps her from hearing, or the threat of a message that her life may change? – Audre Lorde (2007, 125), on being tone-policed by a colleague I am a black woman over six feet tall. My laugh sounds like an exploding mouse. I squeak loudly and speak quickly when I get excited. I like knock in my trunk and bass in my music. . . . I am especially attuned to how my sonic footprint plays into how I live and if I should die. As a black woman, the bulk of my threat is associated with my loudness. – Regina Bradley (2015), on the “sonic disrespectability” of Sandra Bland 1. cops and demons Around noon on August 9, 2014 in Ferguson, Missouri, a white police officer named Darren Wilson fatally shot Michael Brown, an unarmed black teenager. Later, when facing a grand jury, Wilson testified to Brown’s formidable, animalistic attributes: And when I grabbed him [Brown], the only way I can describe it is I felt like a 5-year-old holding onto Hulk Hogan. . . . The only way I can describe it—it looks like a demon. . . . As he is coming towards me, I tell [him], keep telling him to get on the ground, [but] he doesn’t. I shoot a series of shots. . . . At this point, it looked like he was almost bulking up to run through the shots, like it was making him mad that I’m shooting at him. And the face that he had was looking straight through me, like I wasn’t even there, [like] I wasn’t even anything in his way. Well, he keeps coming at me after that again. During the pause I tell him to get on the ground, get on the ground; he still keeps coming at me, gets about 8 to 10 feet away. At this point I’m backing up pretty rapidly. I’m backpedaling pretty good because I know if he reaches me, he’ll kill me. . . . I saw the last one [bullet] go into him. And then when it went into him, the demeanor on his face went blank; the aggression was gone. It was gone—I mean, I knew he stopped. The threat was stopped (State of Missouri v. Darren Wilson, Grand Jury Volume V 2014, 212, 225, 227–28, 228–229).[1] “Demon” wasn’t the “only way” Darren Wilson could have described eighteen-year-old Michael Brown. But the criminalizing epithet helped this officer dodge indictment. For how else should Wilson have reacted when staring down a resilient beast that can charge through bullets? In the courtroom, the locutionary gambit of only way—demon (no alternative words) slid into the self-defense justification of only choice—kill (no alternative actions).[2] Aside from allegedly slinging “fuck,” “pussy,” and other curse words around, this teenager had, according to Wilson, simply uttered “grunting, like, aggravated sound[s]” (227).[3] To the ears and eyes of this cop, Brown was nonverbal (made inchoate noises), nonaural (didn’t listen to orders), nonvisual (looked straight through Wilson).[4] Nonhuman. Wilson’s testimony painted Brown as a thug with impenetrable skin and impenetrable ears. Impenetrable—meaning organs resistant to supersonic bullets and clarion instructions alike. Dehumanizing and deadly consequences spawn from these myths of black bruteness. Multiple recent studies have shown the tendencies of white research subjects to overestimate the size, speed, and age of black people. Such “formidability bias,” scientists argue, can expectedly “[promote] participants’ justifications of hypothetical use of force against Black suspects of crime” (Wilson, Rule, and Hugenberg 2017, 59). Take the tragedy of twelve-year-old Tamir Rice, who, while playing with an Airsoft toy gun in a Cleveland park on November 22, 2014, was shot and killed by police officer Timothy Loehmann.[5] In his signed statement to investigators, Loehmann declared that Rice “appeared to be over 18 years old and about 185 pounds” (Loehmann 2015).[6] Later, in defending Loehmann’s use of lethal force, Cleveland Police Patrolmen’s Association president Steve Loomis likewise urged the public not to trust their own eyes when it came to photos and videos of this pre-teen: “He’s menacing. He’s 5-feet-7, 191 pounds. He wasn’t that little kid . . . you’re seeing in pictures. He’s a twelve-year-old in an adult body” (Stahl 2016).[7] Or was he just a twelve-year-old in a black body? Racist demonstrations of formidability bias similarly broke out in the aftermath of civilian George Zimmerman’s 2012 shooting of the unarmed seventeen-year-old Trayvon Martin in Sanford, Florida (Figure 1). Zimmerman’s supporters complained about the news’ circulation of a photo showing a beaming and “much younger” Martin (Capehart 2013). One defiant reader sent a Washington Post journalist a more “honest” picture that was making the rounds on the Internet, a picture of an “up-to-date” Martin with face tattoos and a sizeable frame (Capehart 2013). Except, it turns out, this wasn’t Trayvon Martin (b. 1995) at all; it was a photo of the rapper Jayceon Terrell Taylor (a.k.a. The Game, b. 1979) (Sanders 2012). Such blatant examples of fake news are usually easy to debunk. Subtler cases of pictorial deceit, however, can prove more elusive yet no less toxic. In April 2012, for instance, people accused Fox News of darkening Trayvon Martin’s skin with Photoshop, a facile manipulation that, as one critic put it, approximated “journalistic lynching” via colorist stigma (Marc NC 2012; Summers 2012). (Several readers likened this case of colorism to the doctored image of O.J. Simpson on a 1994 cover of TIME magazine.)[8] Darker, blacker, meaner, stronger. Formidability myths go beyond overestimations of how resilient black bodies look (exteriorities). These myths concurrently enable underestimations of black bodies’ capacity to feel (interiorities). In a 2014 study, researchers found that white children, beginning as early as age seven, believe their black peers to possess reduced susceptibility to physical pain.[9] Much injustice has historically sprung from white denials of black nociception. “Pain bias,” sometimes called the “racial empathy gap,” is complicit in the societal normalization of black trauma (Wade 2013; Silverstein 2013; Forgiarini, Gallucci, and Maravita 2011).[10] Physicians today prescribe lower and fewer doses of pain medication to black patients, including black children (Hoberman 2012; Hoffman, Trawalter, Axt, and Oliver 2016; Graham 2014). Police use more severe physical force on dark-skinned bodies (Buehler 2017). Therapists, through buy-in of the Strong Black Woman trope, disproportionately trivialize black women’s requests for mental healthcare (West, Donovan, and Daniel 2016). Or we could look back to the era of US chattel slavery, during which white doctors forced black women to undergo childbirth without anesthetic chloroform, even when infants had to be delivered “with the aid of the blunt hook” (Schwartz 2006, 167).[11] Slaveholders’ assumptions that black women were generally “strong enough to endure any pain” further warranted their subjection to every other abuse, including rape (Wyatt 2008, 60; see also Staples 1970). Past and present, these racist fantasies of black painlessness have resonated with what Alexander Weheliye terms the “pernicious logics of racialization,” referring to a “conglomerate of sociopolitical relations that discipline humanity into full humans, not-quite-humans, and nonhumans” (2014, 3).[12] To Weheliye’s taxonomy, we should add the fantastical category of black superhumans—resilient bodies ironically relegated to dehumanized status. Certainly, being bulletproof, like Marvel superhero Luke Cage, could be the devout wish of black people who face police and precarity. Being perceived as bulletproof is the mortal fear.[13] Overestimations of physical and emotional resilience can be curses in disguise.[14] “Stop calling me RESILIENT,” insisted Tracie Washington in her iconic 2005 flyers, which she nailed to telephone poles throughout New Orleans in response to the US media’s coverage of Hurricane Katrina. “Because every time you say, ‘Oh, they’re resilient,’ that means you can do something else to me” (Slater 2014, Figure 2). Don’t explain to me what you think I can survive, proclaimed Washington; ask me what my sunken city needs.[15] Washington’s message should remind us that to mythologize black bodies as indomitable is to reify systems of racist domination. Put differently, professing to know what someone is capable of can risk sliding into neoliberal presumptions of what the person can be subjected to—pain, labor, tribulation, trauma. Obviously, black people are resilient. It’s just that, historically speaking, bad things happen when white people overeagerly celebrate, fetishize, or exploit the obviousness of this notion. Sure, if you’re white, go ahead and admire Strong Black Women, so long as you remember that their strength isn’t for you to test, in the same way their hair isn’t yours to touch. Formidability bias and pain bias together entail an overestimation of black people’s strength, size, age, and resilience—characteristics of physical excess. As a music scholar, I’ve lately wondered how biases about physical excess might intersect and compound with analogous prejudices about black sonic excess. Black people face accusations of protesting too forcefully (Black Lives Matter, “uppity-ism,” the Angry Black Woman), laughing too boisterously (the 2015 Napa Valley wine train skirmish), playing music too loudly (“Jeep Beats” and racial epithets), and shouting in the movie theater (Robinson 2016, 134–58; Cheng 2017, 528–49; Duff 2016; Radano 2000, 459–80).[16] For resentful listeners, black noise is like dirt; it is, to paraphrase the anthropologist Mary Douglas, sonic “matter out of place” (1966, 44).[17] And dirt is an apt simile because, beginning in the nineteenth century, scientific discourses of American hygiene have churned out stigmas of non-white bodies as “dirty” and “impure”—which, as the historian Carl Zimring points out, are viciously hypocritical given how environmental racism (the inequitable allocation of waste and toxins) overwhelmingly harms communities of color (2015, 3–5; see also Godsil 1991; Pulido 2000; Boer, Pastor Jr., Sadd, and Snyder 1997; Casey et al. 2017). Indictments of black sonic impurities ultimately hinge on the following twin assumptions: black bodies make noise; and black ears can take—embrace, withstand, shrug off—noise. Diagnoses of black ears and policings of black noise have often accompanied insidious policies, from the Antebellum South’s pseudo-medical treatises about the auditory “nerves of the Negro” to the present-day fiascos that generate memes of #LaughingWhileBlack, #SingingWhileBlack, and #TalkingWhileBlack (Nott [1844] 1981, 223).[18] Some of these hashtags are meant to be humorous. Far from mere funny business, though, prejudices about black noise can pose grave consequences. Stereotypes about “the ‘deep’ black voice, the ‘noisy’ neighborhood, [and] the ‘loud’ music,” notes the race theorist Jennifer Lynn Stoever, expose “incidents of racist listening [that] cannot be dismissed, laughed off, or chalked up to white ignorance and/or innocence” (2016, 277). Altogether, stereotypes of black physical excess and black sonic excess implicate the threatening physicalities of black sound and, in turn, the threatening sounds of black physicality. In this article, I bear witness to how white misimaginations of black skin, black ears, and black voices in the United States have subtly yet severely abetted racist ideologies that dehumanize, discredit, or outright destroy black life. In the article’s first half, I tug at knotty cultural stereotypes of black resilience and sonic excess. Why are certain expressions of black empowerment deemed respectable, whereas other expressive modes face denunciation and censorship? And how can black-coded musical genres—say, rap, a lynchpin in culture wars—construct and deconstruct myths about the formidability of black bodies? I arrange these primers on resilience, respectability, and rap to triangulate a case study in the article’s latter half, the 2014 criminal trial People of the State of Florida v. Michael David Dunn. Nicknamed the “Loud Music Trial,” this case involved a white civilian named Michael Dunn who, one evening at a Florida gas station, noticed rap music coming from a parked SUV. Dunn approached the SUV and asked the black youths inside the vehicle to turn their music down. When they refused, Dunn launched into a heated argument with one of the boys, a high school student named Jordan Russell Davis. The confrontation ended with Dunn pulling out a handgun, unloading ten rounds, and shooting Davis through the heart. As a high-profile case, People v. Dunn received abundant news coverage in 2014 and served as the subject of a 2015 documentary called 3½ Minutes, 10 Bullets. I have drawn insights from these sources as well as from my own multiple viewings of the complete trial footage.[19] But I’m supplementing this research with materials that eluded mainstream press: Dunn’s jailhouse letters and phone calls (largely omitted from the trial’s formal proceedings); stenographers’ transcriptions of courtroom sidebars (inaudible to gallery members and not picked up by the AV team’s microphones); discovery documents, evidence technicians’ reports, and 9-1-1 records (now publicly available); and my recent conversations with Jordan’s parents, Ron Davis and Lucy McBath. Jordan Davis was 17 years old, 145 pounds, 5’11’’, and unarmed. Michael Dunn was 47 years old, 250 pounds, 6’4’’, and armed. Yet according to Dunn’s testimony, Davis had “threatened my life like a man” and became “louder and louder and more violent and more violent” with every word (Testimony by Defendant 2014, 2956).[20] Or as Dunn told the police: “I didn’t know he was seventeen. I thought he was a full-grown man. I thought they all were. And in my mind they were all going to get out of this truck and shoot me or beat me or kill me” (“Michael Dunn Trial. Day 5. Part 6. Police Interrogation Tape Played,” 4:35:00). Like Michael Brown, Trayvon Martin, and Tamir Rice (forever 18, 17, and 12), Jordan Davis was seen and heard as formidable beyond his years. Perceptions of loud blackness metamorphosed into fictions of criminal threat. Physical and sonic excess made flesh. Flesh unmade by bullets. “I had no choice but to defend myself,” said Dunn. “It was life or death” (Testimony by Defendant 2014, 2958). Only choice—kill. More on People v. Dunn shortly. First, one of the case’s essential themes; or, how resilience has become the new black. Notes See also Halpern (2015) and Travis Jr. (2016, 102–4). Dorian Johnson, who had been walking with Michael Brown, witnessed the altercation. He recalled that Brown, after being struck by Wilson’s first bullet, announced: “I don’t have a gun” (State of Missouri v. Darren Wilson, Grand Jury Volume IV 2014, 123). Wilson testified that Brown had said: “Fuck what you have to say,” “What the fuck are you going to do about it” (State of Missouri v. Darren Wilson, Volume V 2014, 209), and “You are too much of a pussy to shoot me” (214). Wilson claimed he had “[told Brown] to get on the ground, get on the ground,” and that “less than one minute” passed between “[seeing Brown] walking down the street until Michael Brown is dead in the street” (State of Missouri v. Darren Wilson, Grand Jury Volume V 2014, 272). Loehmann claimed he had “ordered Tamir [Rice] three times to show his hands before opening fire,” though several witnesses later came forward to say they had heard no warnings at all (Blackwell 2015). Timothy Loehmann, statement to investigators (signed and dated 30 November 2015). The move to criminalize Rice didn’t simply come from police officers. In an article for CNN, legal analyst Philip Holloway recommended that people “turn to the specific facts,” which include the following: “Tamir Rice, while being a mere 12 years old, appeared much older” (Holloway 2015). For Holloway to classify Rice’s “older” appearance as “fact” is all the more problematic given the author’s legal credentials. See Carmody (1994). Authors summarized their findings as follows: “Five-, 7-, and 10-year-olds first rated the amount of pain they themselves would feel in 10 situations such as biting their tongue or hitting their head. They then rated the amount of pain they believed two other children—a Black child and a White child, matched to the child’s gender—would feel in response to the same events. We found that by age 7, children show a weak racial bias and that by age 10, they show a strong and reliable racial bias” (Dore, Hoffman, Lillard, and Trawalter 2014). See also Trawalter, Hoffman, and Waytz (2012). Instructive though it may be, “racial empathy gap” can nevertheless sound too neutral, absolvent, clinical, and bilateral, as if people of different races simply happen to lack empathy across color lines, and as if dark-skinned bodies aren’t the ones who overwhelmingly pay for such a lack—paying, at times, with their lives. Perhaps a more honest term would be racist empathy gap. In contrast to their poor treatment of black women, the same physicians in the era of US chattel slavery usually “expressed ‘a good deal of solicitude’ for the white woman . . . [and] acted to relieve whatever discomfort she was experiencing” (Schwartz 2006, 166). See also Bourke (2014) and Dudley (2012). In other words, says Weheliye, blackness is a “changing system of unequal power structures that apportion and delimit which humans can lay claim to full human status and which humans cannot” (2014, 3). Empirical studies of “formidability bias” and “pain bias” are complemented by research on the “superhumanization bias” and the “Magic Negro myth.” White research subjects have, in some cases, gone so far as to express beliefs in black people’s ability not only to withstand pain, but also to “suppress hunger or thirst” (Waytz, Hoffman, and Trawalter, 2015, 356). For a similar example, Ana María Ochoa Gautier has noted Alexander von Humboldt’s nineteenth-century documentations of the physical resilience and indecency of the Colombian bogas, the Magdalena River’s boat rowers. As Ochoa Gautier points out, Humboldt’s “positive impression of their tremendous physiques and ‘demonstration of human force’ . . . was muted by the sounds they made,” evidenced by this Prussian explorer’s “repeated use of negative adjectives of excess” such as “barbarous, lustful, angry” (2014, 31–32). In Washington’s plea of “Stop calling me RESILIENT,” then, “calling” is as much of a keyword as “RESILIENT.” To call someone something is to exert implicit control over description, designation, and diagnosis. On the racial politics of “Jeep Beats” and vehicular (black) noise, see Dery (2004, 407–20), Jasen (2016, 6–7), Kelley (1996, 134–35), Rose (1994, 61–62), and Blake (2012, 87–109). For historical perspectives on automobile sound systems, see Morris (2014). In her groundbreaking book on the metaphors and materialities of hygiene (and its opposites), anthropologist Mary Douglas defined dirt as “matter out of place,” or anything that “offends against order” (1966, 44, 2); see also Kapchan (2017, 283). On dirt and blackness, see Fanon (2008, 82–86, 146–47); cf. Read (1996). See also Smith (2006, 33–34), Kennaway (2016, 117–19), Chang (2016, 69–70), Markus (2015), and CTVNews.ca Staff (2017). All cameras in the courtroom belonged to the documentary filmmakers for 3½ Minutes, 10 Bullets. Full recordings of the trial and the retrial are available online and are cited in this article accordingly. I am grateful to Ron Davis, who has worked closely with the 3½ Minutes, 10 Bullets team, for helping obtain access and permissions to original footage. References to People of the State of Florida v. DUNN MICHAEL DAVID are hereafter abbreviated as People v. Dunn.